The Role of Pondok Pesantren Tohir Yasin in the Empowerment of Community Economy - Syahrullah, S.; Ridwan Mas'ud; Zulpawati, Z. (Golden Ratio of Social Science and Education, 2025)
This study discusses the strategic role of Pondok Pesantren Thohir Yasin in community economic empowerment through a community-based approach. Amidst the economic crisis and social inequality caused by less inclusive state policies, the pesantren emerges as an alternative solution by integrating religious values with grassroots economic strengthening. Using a qualitative case study approach, this research examines various empowerment programs, including job creation, MSME development, and community-based health services. The findings indicate that the pesantren has successfully acted as a social transformation agent, directly improving the community's standard of living. It not only strengthens institutional independence but also promotes sustainable local economic growth. This study emphasizes the importance of the communal economic model as a middle ground between liberal and socialist economic systems, while highlighting the need for institutional and managerial strengthening to ensure sustainable and inclusive empowerment.